Pomeranian farmers, populations vulnerable to skin cancer in Espírito Santo: Report on the experience of teaching-service-community integration - de Cássia Cunha Rocha, Rita; Auler, João Paulo; Soares de Barros, Luis Fernando; de Medeiros Cazelli, Wallace (Guará Journal, 2025)
For approximately three decades, the Dermatological Assistance Program for Pomeranian Farmers of Espírito Santo has been a setting for teaching, service, and community collaboration. The program aims to publicize the involvement of Federal University of Espírito Santo students in eleven communities vulnerable to skin cancer, enabling training focused on the concrete realities and needs of the Unified Health System, experienced through extramural practice. The methodology used was experience reporting with a literature review. The institutional partnership, as a strategy for developing student skills and patient care, was significant in the results achieved.